Novel Technologies for Vaccine Development - Lukashevich, Igor S.; Lukashevich, Igor S.; Shirwan, Haval.; Shirwan, Haval. (Springer Vienna : Imprint: Springer, 2014)
This book presents a detailed overview of the development of new viral vector-based vaccines before discussing two major applications: preventive vaccines for infectious diseases and therapeutic cancer vaccines. Viral vector-based vaccines hold a great potential for development into successful pharmaceutical products and several examples at the advanced pre-clinical or clinical stage are presented. Nevertheless, the most efforts were focused on novel and very innovative technologies for new generation of vector-based vaccines. Furthermore, specific topics such as delivery and adjuvant and protection strategies for cell-mediated-based vaccines are presented. Given its scope, the book is a “must read” for all those involved in vaccine development, both in academia and industrial vaccine development.